2009
DOI: 10.1080/15700760902737162
|View full text |Cite
|
Sign up to set email alerts
|

School Leaders' Problem Framing: A Sense-Making Approach to Problem-Solving Processes of Beginning School Leaders

Abstract: In addition to cognitive research on school leaders' problem solving, this study focuses on the situated and personal nature of problem framing by combining insights from cognitive research on problem solving and sense-making theory. The study reports the results of a case study of two school leaders solving problems in their daily context by using a sense-making approach. Detailed analysis of school leaders' problem-solving processes shows how the way school leaders frame the problems they are dealing with is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Apart from the influence of the principal preparation programme (Holligan et al 2006), gender discrimination (Dunshea 1998) and the NP's professional biography (Sleegers et al 2009), much significance has been attributed to the support and guidance NPs receive in their work for their career development and professional socialization. It was found that NPs receive support from a wide variety of sources, including their district, peers, staff, administrative team, professional networks, governors, parents, family, community, role models, friends and even the former principal of the NP when the NP was a teacher , Osterman and Sullivan 1996, Cheung and Walker 2006, Crow 2007, Kelly and Saunders 2010.…”
Section: Determinants Affecting the Early Career Stage Of Principalshipmentioning
confidence: 99%
“…Apart from the influence of the principal preparation programme (Holligan et al 2006), gender discrimination (Dunshea 1998) and the NP's professional biography (Sleegers et al 2009), much significance has been attributed to the support and guidance NPs receive in their work for their career development and professional socialization. It was found that NPs receive support from a wide variety of sources, including their district, peers, staff, administrative team, professional networks, governors, parents, family, community, role models, friends and even the former principal of the NP when the NP was a teacher , Osterman and Sullivan 1996, Cheung and Walker 2006, Crow 2007, Kelly and Saunders 2010.…”
Section: Determinants Affecting the Early Career Stage Of Principalshipmentioning
confidence: 99%
“…Collectively, this literature indicates that educators' policy responses are largely driven by their prior knowledge, beliefs, and values, often resulting in implementation variation. Others have applied this lens to the study of education leaders' problem-solving (Sleegers et al 2009) and how they think about race and social justice (DeMatthews 2015;Evans 2007). In this article, we blend these approaches and extend this lens to analyze district administrators' responses to equity-oriented finance policy.…”
Section: Sensemakingmentioning
confidence: 99%
“…These developments together with changes in the organisational and governance structure of schools have increased the diversity and variability connected with these jobs (Hulpia and Devos 2009;Sleegers et al 2011). School administrators who have built leadership capacity among the staff at their schools established a culture of trust, honesty and professionalism, and facilitated teacher leadership (Mullen and Jones 2008).…”
Section: Leadership and Inclusionmentioning
confidence: 98%